Concerns and Suspicions on a Questionable Science in the Era of Ideologies: The Hard Pathway of Comparative Education in Italy during the 1970s - Todaro, Letterio (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación)

(untitled) (Faculty of Education, Queen's University, 2020)
Up until the 1970s, comparative research on education had been scarcely developed in Italy. The rise of a general attention on the promising chances offered by the comparative inquiries in educational sciences was mainly due to the growing influence of several international institutions and organizations in framing a number of studies and reports on the educational process within a comparative perspective. However, the development of comparative education also met resistances and constraints in the Italian framework. A lot of critical voices rising from radical, neo-Marxist, and “not aligned” cultures questioned the alleged impartiality of the comparative discipline, expounding serious concern about the legitimacy of its scientific pretensions. On the whole, the outstanding critical views on the rise of comparative education fostered a wide suspicion of the influence of global agents in assessing the goals of education and particularly of the role of the main international organizations leading the strategies for global development.